A Qualitative Study of the System-level Barriers to Bariatric Surgery Within the Veterans Health Administration. Issue 1 (January 2022) - Funk, Luke M.; Alagoz, Esra; Jolles, Sally A.; Shea, Grace E.; Gunter, Rebecca L.; Raffa, Susan D.; Voils, Corrine I.
Abstract : Objective: To characterize system-level barriers to bariatric surgery from the perspectives of Veterans with severe obesity and obesity care providers. Summary of Background Data: Bariatric surgery is the most effective weight loss option for Veterans with severe obesity, but fewer than 0.1% of Veterans with severe obesity undergo it. Addressing low utilization of bariatric surgery and weight management services is a priority for the veterans health administration. Methods: We conducted semi-structured interviews with Veterans with severe obesity who were referred for or underwent bariatric surgery, and providers who delivered care to veterans with severe obesity, including bariatric surgeons, primary care providers, registered dietitians, and health psychologists. We asked study participants to describe their experiences with the bariatric surgery delivery process in the VA system. All interviews were audio-recorded and transcribed. Four coders iteratively developed a codebook and used conventional content analysis to identify relevant systems or "contextual" barriers within Andersen Behavioral Model of Health Services Use. Results: Seventy-three semi-structured interviews with veterans (n = 33) and providers (n = 40) throughout the veterans health administration system were completed. More than three-fourths of Veterans were male, whereas nearly three-fourths of the providers were female. Eight themes were mapped onto Andersen model as barriers to bariatric surgery: poor care coordination, lack of bariatric surgery guidelines, limited primary care providers and referring provider knowledge about bariatric surgery, long travel distances, delayed referrals, limited access to healthy foods, difficulties meetings preoperative requirements, and lack of provider availability and/or time. Conclusions: Addressing system-level barriers by improving coordination of care and standardizing some aspects of bariatric surgery care may improve access to evidence-based severe obesity care within VA. Abstract : Supplemental Digital Content is available in the text